2017
DOI: 10.1177/0022022117692675
|View full text |Cite
|
Sign up to set email alerts
|

Does Contextual Change Affect Basic Human Values? A Dynamic Comparative Multilevel Analysis Across 32 European Countries

Abstract: This article examines the relationship of stable contextual differences and contextual change with the endorsement of Schwartz’s (1992) two basic value dimensions—Openness-to-Change versus Conservation and Self-Enhancement versus Self-Transcendence. Using six waves of the European Social Survey, an extension of multilevel analysis is used which combines both a cross-national comparative and a dynamic analysis of values. The hierarchical data structure and the covariates for value endorsement are defined at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 49 publications
1
43
2
2
Order By: Relevance
“…Past research that examined only the higher order values and included the entire age range in ESS samples revealed little change in personal values (Tormos et al, 2017). The current study uncovered greater change by (a) studying young people, whose values are theoretically more malleable, and (b) by studying the 10 single values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research that examined only the higher order values and included the entire age range in ESS samples revealed little change in personal values (Tormos et al, 2017). The current study uncovered greater change by (a) studying young people, whose values are theoretically more malleable, and (b) by studying the 10 single values.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the United Kingdom found increased security–conformity values after 2008 (Austin, 2016). A study across six waves of the European Social Survey (ESS) found high-value stability (Tormos, Vauclair, & Dobewall, 2017). However, these studies investigated the general (adult) population and did not consider the special impact the GFC could have on young people.…”
Section: Basic Personal Valuesmentioning
confidence: 99%
“…When examining the association between cultural value orientations and alcohol consumption at different years we used the same CVO values and so it might be argued that our results do not entirely accurately reflect the time specific associations. However, cultural value orientations are claimed to be stable over time ( Schwartz et al, 2000 ; Hofstede, 2001 ; Manfredo et al, 2017 ; Tormos et al, 2017 ) and this suggests that over a relatively short period of time using the same values of cultural value orientations is legitimate.…”
Section: Discussionmentioning
confidence: 99%
“…Según esta teoría, el cambio de valores ocurre de forma lenta y progresiva, fundamentalmente a través del reemplazo generacional y de la asimilación y adaptación lenta a nuevas condiciones materiales, ambientales y culturales (Inglehart, 1977(Inglehart, , 1990Inglehart y Welzel, 2005). Esta estabilidad de los valores contrasta con la visión de otros estudios que los presentan como más sensibles a situaciones cambiantes (Tormos et al, 2017). Algunos estudios sugieren que los valores pueden ser alterados fruto de situaciones de transición relevantes como migraciones o sucesos fortuitos o traumáticos como guerras (Daniel et al, 2013).…”
Section: Formación Y Cambio De Valoresunclassified